Manganese-based catalyst for efficiently degrading formaldehyde at room temperature and preparation method thereof
By synthesizing the MnOx@MOy composite catalyst, the problem that existing technology is difficult to efficiently degrade formaldehyde at room temperature is solved, achieving efficient and low-cost formaldehyde degradation effect, and having good cycle stability.
Patent Information
- Application Number
- CN202411420799.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to efficiently degrade formaldehyde at room temperature, and the high cost of precious metal-based catalysts limits their wide application.
The MnOx@MOy composite catalyst is synthesized through one-step hydrothermal method, metering titration or stirring method combined with thermal decomposition method. The catalyst is prepared by the reaction of Mn2+, alkali metal ions and third metal ions, and can efficiently degrade formaldehyde at room temperature.
It achieves efficient degradation of formaldehyde at room temperature with high degradation rate and low cost. It has potential industrial value and the catalyst has good cycle stability.
Smart Images

Figure CN119327445A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of indoor pollution control, environmental protection and material technology, and specifically relates to a manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof. Background Art
[0002] The widespread use of building and decoration materials has led to formaldehyde becoming one of the main indoor pollutants. Long-term exposure to formaldehyde environment will cause serious harm to human health. Even at low concentrations (<0.5ppm), it will cause serious irritation, such as central nervous system damage, respiratory diseases, and even cancer. In the process of catalytic degradation of indoor formaldehyde gas, the humidity of formaldehyde gas needs to be maintained at 50%-70%. Therefore, absorbing formaldehyde in indoor air into water to form a solution, adding a catalyst to the solution to degrade it, is expected to achieve effective control of indoor formaldehyde.
[0003] Formaldehyde catalytic oxidation mainly uses precious metal materials and transition metal oxides as catalysts. Precious metal-based catalysts can completely convert formaldehyde into CO at near room temperature. 2 and H 2 O, but high cost is the biggest obstacle to its widespread application. Transition metal oxide catalysts are gaining more and more attention in low-temperature formaldehyde degradation due to their high catalytic efficiency, non-toxicity and low cost.
[0004] To this end, this patent uses CO at room temperature and normal pressure. 2 SM, Mn 2+ 、M y+ and alkali metal ions as raw materials, and the A-MnOx@MOy composite catalyst was synthesized by a one-step hydrothermal method, a metering titration method or a stirring method combined with thermal decomposition. This process achieved efficient degradation of formaldehyde at room temperature, which has practical significance for the development of low-temperature catalytic degradation of formaldehyde technology. Summary of the invention
[0005] The invention discloses a manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof. 2+ , alkali metal ions (A = Na + , K + , Li + or Cs + ) and the third metal ion (M y+ =Zn 2+ 、Cd 2+ 、Ni 2+ , Gd 3+ , Pr 3+ 、Sm 3 + 、Nd 3+ 、Ce 3+or La 3+ ) reaction, which can efficiently degrade formaldehyde under room temperature conditions.
[0006] The present invention provides a manganese-based catalyst for efficiently degrading formaldehyde at room temperature. The degradation rate of the catalyst for formaldehyde solution is increased by doping transition metals or rare earth elements and alkali metal elements, and a new technology is provided for the design of a catalyst for degrading formaldehyde at room temperature. The catalyst has potential industrial value in terms of environmental protection and economic benefits. The manganese-based catalyst for efficiently degrading formaldehyde at room temperature provided by the present invention can be recycled and has good cycle stability.
[0007] The manganese-based catalyst for efficiently degrading formaldehyde at room temperature and the preparation method thereof, specifically comprises the following steps:
[0008] 1-step hydrothermal method and thermal decomposition method:
[0009] 1) Add 50mL (0.03~0.40)mol / L Mn 2+ Solution, n M / n Mn =(0~0.3) and (0.5-5.0) g CO 2 SM is mixed and stirred to form a mixed solution;
[0010] 2) The mixed solution in step 1) is placed in a high pressure reactor, hydrothermal at 120°C for 1 to 5 hours, filtered, washed and dried to obtain MnCO 3 @M(CO 3 )y precursor, weigh the solid mass;
[0011] 3) MnCO obtained in step 2) 3 @M(CO 3 )y precursor, calcined at 280-400℃ for 2-10h in air atmosphere to obtain ε-MnO 2 @MOy composite catalyst;
[0012] 4) Impregnating the MnCO in step 2) with alkali metal ions 3 @M(CO 3 )y precursor is calcined at 280-400°C for 2-10h in an air atmosphere to obtain an A-MnOx@MOy composite catalyst.
[0013] 2. Metering titration and thermal decomposition method:
[0014] 1) Place 50mL (0.5~1.5)mol / L Mn 2+ The solution was placed in a water bath at 80°C;
[0015] 2) Add 50mL (0.01~0.05)mol / LM x+solution and 50mL (80-220)g / L CO 2 The SM solution is dripped into the solution in step 1) at a certain dripping rate through a microinjection pump. After reacting for 1 to 5 hours, it is filtered, washed, and dried to obtain MnCO 3 @M(CO 3 )y precursor;
[0016] 3) MnCO obtained in step 2) 3 @M(CO 3 )y precursor, calcined at 280-400℃ for 2-10h in air atmosphere to obtain ε-MnO 2 @MO y Composite catalyst;
[0017] 4) Impregnating the MnCO in step 2) with alkali metal ions 3 @M(CO 3 )y precursor is calcined at 280-400°C for 2-10h in an air atmosphere to obtain an A-MnOx@MOy composite catalyst.
[0018] 3. Stirring method and thermal decomposition method:
[0019] 1) At room temperature, 50 mL (0.5-1.5) mol / L Mn 2+ Solution, 50mL (0.01~0.05) mol / LM y+ solution and 50mL (80-220)g / L CO 2 The SM solution was mixed and stirred, reacted for 1 to 5 hours, filtered, washed and dried to obtain MnCO 3 @M(CO 3 )y precursor;
[0020] 2) MnCO obtained in step 1) 3 @M(CO 3 )y precursor, calcined at 280-400℃ for 2-10h in air atmosphere to obtain ε-MnO 2 @MOy composite catalyst;
[0021] 3) Impregnating the MnCO in step 1) with alkali metal ions 3 @M(CO 3 ) y The precursor is calcined at 280-400° C. for 2-10 h in an air atmosphere to obtain an A-MnOx@MOy composite catalyst.
[0022] The MnOx@MOy composite catalyst and the A-MnOx@MOy composite catalyst prepared by the present invention have a high degradation rate for formaldehyde in a closed device at normal pressure and 30°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0024] Figure 1 (ε-MnO prepared in Example 1 2 / CeO 2 )@CeO 2 With ε-MnO 2 、CeO 2 Comparative XRD patterns;
[0025] Figure 2 (ε-MnO prepared in Example 1 2 / CeO 2 )@CeO 2 SEM images of
[0026] Figure 3 K-Mn obtained in Example 2 3 O 4 @CeO 2 SEM images of
[0027] Figure 4 K-Mn obtained in Example 2 3 O 4 @CeO 2 Cyclic degradation formaldehyde stability test diagram. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific examples, but the protection scope of the present invention is not limited thereto. A specific embodiment of a manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof is as follows:
[0029] Embodiment 1:
[0030] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0031] 2) Weigh 3g CO 2 SM and 0.2 g CeCl 3 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0032] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0033] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0034] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @CeCO 3 OH solid;
[0035] 6) The MnCO obtained in step 5) 3 @CeCO 3 OH solid was calcined at 320℃ for 6h in air atmosphere to obtain (ε-MnO 2 / CeO 2 )@CeO 2 Composite catalyst.
[0036] The (ε-MnO 2 / CeO 2 )@CeO 2 The composite catalyst was tested by XRD and SEM. Figure 1 The (ε-MnO 2 / CeO 2 )@CeO 2 XRD pattern of Figure 2 The (ε-MnO 2 / CeO 2 )@CeO 2 From the SEM image, we can see that (ε-MnO 2 / CeO 2 )@CeO 2 The sample appeared as spherical particles. When the degradation time was 1h and the degradation temperature was 30℃, the degradation rate of 10mL 10mg / L HCHO solution was 54.9%, and when the degradation time reached 16h, the degradation rate was 91.2%.
[0037] Embodiment 2:
[0038] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0039] 2) Weigh 2g CO 2 SM and 0.3 g CeCl 3 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0040] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0041] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0042] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @CeCO 3 OH solid;
[0043] 6) Immerse K ions into the MnCO 3 @CeCO 3 OH solid was calcined at 340℃ for 6h in air atmosphere to obtain K-Mn 3 O 4 @CeO 2 Composite catalyst.
[0044] The K-Mn prepared in Example 2 3 O 4 @CeO 2 The composite catalyst was subjected to SEM and cycle stability tests. Figure 3 K-Mn prepared in Example 2 3 O 4 @CeO 2 From the SEM image, we can see that K-Mn 3 O 4 @CeO 2 The composite catalyst is in the form of spherical particles. Figure 4 K-Mn prepared in Example 2 3 O 4 @CeO 2 Cyclic stability test diagram, by Figure 4 It can be seen that K-Mn 3 O 4 @CeO 2 The composite catalyst has good cyclic stability. When the degradation time is 1h and the degradation temperature is 30℃, K-Mn 3 O 4 @CeO 2The degradation rate of the catalyst for 10mL10mg / L HCHO solution is 94.1%. After 10 cycles, the degradation rate in 1h is still maintained at 82.3%, and the catalyst has good stability. The degradation rate for 10mL40mg / L HCHO solution is 65.8%. When the degradation time reaches 14h, the degradation rate is 99.3%.
[0045] Embodiment 3:
[0046] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0047] 2) Weigh 4g CO 2 SM and 0.2 g C 6 H 9 LaO 6 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0048] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0049] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0050] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @La 2 (CO 3 ) 3 solid;
[0051] 6) The MnCO obtained in step 5) 3 @La 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain ε-MnO 2 @La 2 O 3 Composite catalyst.
[0052] 7) Immerse K ions into the MnCO 3 @La 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain K-ε-MnO 2 @La2 O 3 Composite catalyst.
[0053] When the degradation time is 1h and the degradation temperature is 30℃, K-ε-MnO 2 @La 2 O 3 The degradation rate of the catalyst for 10 mL of 10 mg / L HCHO solution was 81.1%, and the degradation rate for 10 mL of 40 mg / L HCHO solution was 54.8%. When the degradation time reached 16 h, the degradation rate was 91.2%. Example 4:
[0054] 1) Weigh 22.1g C 4 H 6 MnO 4 , 1.01 g CeCl 3 and 18 g CO 2 SM, add deionized water to 100 mL, and obtain C 4 H 6 MnO 4 、CeCl 3 and CO 2 SM solution;
[0055] 2) Place 50 mL of C 4 H 6 MnO 4 The round-bottom flask containing the solution was placed in a water bath at 80°C;
[0056] 3) Add 50 mL CeCl 3 solution and 50 mL CO 2 The SM solution was dripped into C at a certain drip rate through a microinjection pump. 4 H 6 MnO 4 Solution, reaction for 3h;
[0057] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0058] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @CeCO 3 OH solid;
[0059] 6) The MnCO obtained in step 5) 3 @CeCO 3 OH solid was calcined at 360℃ for 8h in air atmosphere to obtain ε-MnO 2 @CeO 2 Composite catalyst.
[0060] 7) Immerse Cs ions into the MnCO 3 @CeCO 3 OH solid was calcined at 340℃ for 6h in air atmosphere to obtain Cs-ε-MnO 2 @CeO 2 Composite catalyst.
[0061] When the degradation time is 1h and the degradation temperature is 30℃, Cs-ε-MnO 2 @CeO 2 The degradation rate of the catalyst for 10mL 10mg / L HCHO solution was 81.1%, and the degradation rate for 10mL 40mg / L HCHO solution was 54.8%. When the degradation time reached 16h, the degradation rate reached 91.2%.
[0062] Embodiment 5:
[0063] 1) Weigh 22.1g C 4 H 6 MnO 4 , 0.82 g C 4 H 6 CdO 4 and 18 g CO 2 SM, add deionized water to 100 mL, and obtain C 4 H 6 MnO 4 , C 4 H 6 CdO 4 and CO 2 SM solution;
[0064] 2) taking 50 mL of the solution in step 1), respectively, mixing and stirring, and reacting in a water bath at room temperature for 4 h;
[0065] 3) filtering the solution in step 2) to obtain a milky white or light pink precipitate, and washing the precipitate with deionized water and anhydrous ethanol for 3 times;
[0066] 4) The precipitate obtained in step 3) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @CdCO 3 solid;
[0067] 5) The MnCO obtained in step 4) 3 @CdCO 3 Solid was calcined at 360℃ for 8h in air atmosphere to obtain ε-MnO 2 @CdO composite catalyst.
[0068] 6) Immerse Li ions into the MnCO 3 @CdCO 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain Li-ε-MnO 2 @CdO composite catalyst.
[0069] When the degradation time is 1h and the degradation temperature is 30℃, Li-ε-MnO 2 The degradation rate of @CdO catalyst for 10mL 10mg / L HCHO solution is 86.2%, and the degradation rate for 10mL 30mg / L HCHO solution is 62.7%. When the degradation time reaches 16h, the degradation rate is 89.3%.
[0070] Embodiment 6:
[0071] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0072] 2) Weigh 3g CO 2 SM and 0.2g PrN 3 O 9 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0073] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0074] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0075] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @Pr 2 (CO 3 ) 3 solid;
[0076] 6) The MnCO obtained in step 5) 3 @Pr 2 (CO 3 ) 3 Solid was calcined at 320℃ for 8h in air atmosphere to obtain ε-MnO 2 @Pr 2 O 3 Composite catalyst.
[0077] 7) Immerse K ions into the MnCO 3 @Pr 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain K-ε-MnO 2 @Pr 2 O 3 Composite catalyst.
[0078] When the degradation time is 1h and the degradation temperature is 30℃, K-ε-MnO 2 @Pr 2 O 3 The degradation rate of the catalyst for 10mL 10mg / L HCHO solution was 86.5%, and the degradation rate for 10mL 40mg / L HCHO solution was 75.6%. When the degradation time reached 14h, the degradation rate was 85.4%.
[0079] Embodiment 7:
[0080] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0081] 2) Weigh 3g CO 2 SM and 0.2 g SmCl 3 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0082] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0083] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0084] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @Sm 2 (CO 3 ) 3 solid;
[0085] 6) The MnCO obtained in step 5) 3 @Sm 2 (CO 3 ) 3 Solid was calcined at 360℃ for 6h in air atmosphere to obtain ε-MnO 2@Sm 2 O 3 Composite catalyst.
[0086] 7) Immerse Li ions into the MnCO 3 @Sm 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain Li-ε-MnO 2 @Sm 2 O 3 Composite catalyst.
[0087] When the degradation time is 1h and the degradation temperature is 30℃, Li-ε-MnO 2 @Sm 2 O 3 The degradation rate of the catalyst for 10mL 10mg / L HCHO solution was 75.4%, and the degradation rate for 10mL 40mg / L HCHO solution was 65.4%. When the degradation time reached 14h, the degradation rate was 84.6%.
[0088] Embodiment 8:
[0089] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0090] 2) Weigh 1g CO 2 SM and 0.1gNd(CH 3 CO 2 ) was placed in a 100 mL reaction kettle, and 50 mL of the solution obtained in step 1) was added;
[0091] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0092] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0093] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @Nd 2 (CO 3 ) 3 solid;
[0094] 6) The MnCO obtained in step 5) 3@Nd 2 (CO 3 ) 3 Solid was calcined at 360℃ for 8h in air atmosphere to obtain ε-MnO 2 @Nd 2 O 3 Composite catalyst.
[0095] 7) Immerse K ions into the MnCO 3 @Nd 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain K-ε-MnO 2 @Nd 2 O 3 Composite catalyst.
[0096] When the degradation time is 1h and the degradation temperature is 30℃, K-ε-MnO 2 @Nd 2 O 3 The degradation rate of the catalyst for 10mL 10mg / L HCHO solution was 74.5%, and the degradation rate for 10mL 40mg / L HCHO solution was 53.4%. When the degradation time reached 14h, the degradation rate was 82.3%.
[0097] Embodiment 9:
[0098] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0099] 2) Weigh 5g CO 2 SM and 0.2 g C 6 H 9 GDj 6 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0100] 3) reacting the reactor in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0101] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0102] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @Gd2 (CO 3 ) 3 solid;
[0103] 6) The MnCO obtained in step 5) 3 @Gd 2 (CO 3 ) 3 Solid was calcined at 320℃ for 6h in air atmosphere to obtain ε-MnO 2 @Gd 2 O 3 Composite catalyst.
[0104] 7) Immerse Cs ions into the MnCO 3 @Gd 2 (CO 3 ) 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain Cs-ε-MnO 2 @Gd 2 O 3 Composite catalyst.
[0105] When the degradation time is 1h and the degradation temperature is 30℃, Cs-ε-MnO 2 @Gd 2 O 3 The degradation rate of the catalyst for 10 mL of 10 mg / L HCHO solution was 69.4%, and the degradation rate for 10 mL of 40 mg / L HCHO solution was 43.5%. When the degradation time reached 14 h, the degradation rate was 74.5%. Example 10:
[0106] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H1 6 MnO 4 Solution;
[0107] 2) Weigh 2g CO 2 SM and 0.4gNiC 4 H 6 O 4 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0108] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0109] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0110] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @NiCO 3 solid;
[0111] 6) The MnCO obtained in step 5) 3 @NiCO 3 Solid was calcined at 320℃ for 6h in air atmosphere to obtain ε-MnO 2 @NiO composite catalyst.
[0112] 7) Immerse Cs ions into the MnCO 3 @NiCO 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain Cs-ε-MnO 2 @NiO composite catalyst.
[0113] When the degradation time is 1h and the degradation temperature is 30℃, Cs-ε-MnO 2 @NiO catalyst has a degradation rate of 70.5% for 10mL 10mg / L HCHO solution and 51.4% for 10mL 40mg / L HCHO solution. When the degradation time reaches 14h, the degradation rate is 81.6%.
[0114] Embodiment 11:
[0115] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0116] 2) Weigh 5gCO 2 SM and 0.1g ZnCl 2 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0117] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0118] 4) filtering the solution in step 3) to obtain a milky white or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0119] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @ZnCO 3 solid.
[0120] 6) Immerse K ions into the MnCO 3 @ZnCO 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain K-ε-MnO 2 @ZnO composite catalyst.
[0121] When the degradation time is 1h and the degradation temperature is 30℃, K-ε-MnO 2 @The degradation rate of ZnO catalyst for 10mL 10mg / g / L HCHO solution is 69.6%, and the degradation rate for 10mL 40mg / L HCHO solution is 46.2%. When the degradation time reaches 14h, the degradation rate is 74.6%.
[0122] Embodiment 12:
[0123] 1) Weigh 19.3 g C4H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0124] 2) Weigh 1g CO 2 SM and 0.2 g C 4 H 6 CdO 4 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0125] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a dark brown or light pink precipitate;
[0126] 4) filtering the solution in step 3) to obtain a dark brown or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0127] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 @CdCO 3 solid.
[0128] 6) The MnCO obtained in step 5) 3 @CdCO 3 Solid was calcined at 320℃ for 6h in air atmosphere to obtain ε-MnO 2 @CdO composite catalyst
[0129] 7) Immerse Li ions into the MnCO 3 @CdCO 3Solid was calcined at 340℃ for 6h in air atmosphere to obtain Li-ε-MnO 2 @CdO composite catalyst.
[0130] When the degradation time is 1h and the degradation temperature is 30℃, Li-ε-MnO 2 The degradation rate of @CdO catalyst for 10mL 10mg / L HCHO solution is 91.3%, and the degradation rate for 10mL 100mg / L HCHO solution is 70.5%. When the degradation time reaches 14h, the degradation rate is 95.1%.
[0131] Embodiment 13:
[0132] 1) Weigh 19.3 g C 4 H 6 MnO 4 , add deionized water to 250mL to obtain C 4 H 6 MnO 4 Solution;
[0133] 2) Weigh 2g CO 2 SM and 0.2 g C 4 H 6 CdO 4 Place in a 100 mL reaction kettle and add 50 mL of the solution obtained in step 1);
[0134] 3) reacting the reaction kettle in step 2) at 120° C. for 2 h to form a solution containing a milky white or light pink precipitate;
[0135] 4) filtering the solution in step 3) to obtain a dark brown or light pink precipitate, and washing it with deionized water and anhydrous ethanol for 3 times;
[0136] 5) The precipitate obtained in step 4) was dried at 120°C for 2 h to obtain MnCO with a spherical structure. 3 / CdCO 3 solid.
[0137] 6) Immerse Na ions into the MnCO 3 @CdCO 3 Solid was calcined at 340℃ for 6h in air atmosphere to obtain Na-ε-MnO 2 @CdO composite catalyst.
[0138] At room temperature and pressure, the Na-ε-MnO 2The process and performance of 10mL 100mg / L formaldehyde solution catalytically degraded by @CdO composite catalyst are as follows: 10mL 100mg / L HCHO solution is transferred into two 50mL reactors with a 10mL pipette; the two reactors are placed in a constant temperature water bath, and after reaching a constant temperature, 0.05g catalyst is added to one of the reactors, and the reactor without catalyst is used as a blank control; after reacting for 14h, the two HCHO solutions are filtered with a water filter membrane with a pore size of 0.22μm; the filtrate is placed in a stoppered colorimetric tube, 2.5mL of color developer is added, and the color development reaction is carried out in a constant temperature water bath at (60±2)℃ for 15min; after the color development reaction is completed, it is placed at room temperature and cooled for 1h, and the absorbance is measured at a wavelength of 414nm. The degradation rate of HCHO solution is 94.86%, and the cyclic degradation performance is good, indicating that Na-(ε-MnO 2 / CdO)@ε-MnO 2 The composite catalyst has the ability to efficiently catalyze the degradation of HCHO at room temperature.
Claims
1. A manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof, characterized in that: The catalyst is an A-MnOx@MOy composite catalyst, which is composed of a carbon dioxide storage material (CO2SM, ZL201410578343.6), Mn 2+ , alkali metal ions (A = Na + , K + , Li + or Cs + ) and the third metal ion (M y+ =Zn 2+ 、Cd 2+ ,La 2+ , Gd 3+ , Pr 3+ 、Sm 3+ 、Nd 3+ 、Ce 3+ or La 3 + ) reaction, and its microscopic morphology has a nanostructure.
2. A manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof according to claim 1, characterized in that: 1) One-step hydrothermal / thermal decomposition method is to add 50mL (0.03~0.40)mol / L Mn 2+ Solution, n M / n Mn = (0-0.3) g and (0.5-5.0) g CO2SM, mixed and stirred to form a mixed solution, placed in a reaction kettle, reacted at 120°C for 1-5 h, filtered, washed, and dried to obtain MnCO3@M(CO3)y precursor spherical particles; 2) The quantitative titration / thermal decomposition method is to add 50mL (0.5~1.5)mol / L Mn 2+ The solution was placed in a water bath at 80°C; 50 mL (0.01-0.05) mol / LM y+ The solution and 50 mL (80-220) g / L CO2SM solution were dripped at a certain dripping rate through a microinjection pump, and after reacting for 1-5 h, the mixture was filtered, washed, and dried to obtain a MnCO3@M(CO3)y precursor; 3) Stirring method / thermal decomposition method is to mix 50mL (0.5~1.5)mol / L Mn 2+ Solution, 50mL (0.01~0.05) mol / LM y+ The solution was mixed with 50 mL (80-220) g / L CO2SM solution, stirred, reacted for 1-5 h, filtered, washed, and dried to obtain a MnCO3@M(CO3)y precursor; 4) calcining the MnCO3@M(CO3)y precursor of step 1), 2) or 3) at 280-400° C. for 2-10 h in an air atmosphere to obtain a MnOx@MOy composite catalyst; 5) Alkali metal ions A are impregnated into the MnCO3@M(CO3)y precursor of step 1), 2) or 3), and calcined at 280-400°C for 2-10h in an air atmosphere to obtain an A-MnOx@MOy composite catalyst.
3. A manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof according to claim 2, characterized in that In step 1), 2) or 3), Mn 2+ It is manganese chloride, manganese nitrate, manganese sulfate or manganese acetate. The metal ions include Zn 2+ 、Cd 2+ 、Ni 2+ , Gd 3+ , Pr 3+ 、Sm 3+ 、Nd 3+ 、Ce 3+ or La 3+ .
4. A manganese-based catalyst for efficiently degrading formaldehyde at room temperature and a preparation method thereof according to claim 2, characterized in that In step 4), the alkali metal ion is Na + , K + , Li + or Cs + .
Citation Information
Cited By
Preparation method of composite catalyst for synthesizing 1, 4-butynediol
CN119500147A